2021
DOI: 10.21098/jimf.v7i4.1271
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Intention to Accept Shariah Compliant Crowdfunding Mode of Financing in Borno State, Nigeria

Abstract: Micro-, small and medium-sized enterprises (MSMEs) face numerous obstacles, such as a lack of funding, which hinder their growth and expansion. They must have access to long-term funding to improve and modernise their operations competitively. This study aims to incorporate Shariah-compliant crowd funding among MSMEs in Borno state of Nigeria. It applies partial least squares  structural equation modelling (PLS-SEM) on a sample of 341 MSMEs and recommends the need to educate and enlighten them about the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
(43 reference statements)
1
4
0
2
Order By: Relevance
“…These results are interesting for the SCF industry as a whole, because previous studies regarding motivation to utilize Islamic fintech products and services, such as Majid (2021), Darmansyah et al (2020), Purwantini et al (2020), andNiswah et al (2019), found that ATB had no significant effect on BI. In fact, Majid & Nugraha (2022) tested the intention of potential investors to invest through SCF in Indonesia and found the same result, as did Sulaiman et al (2021) when testing the intention to employ syariah-compliant crowdfunding in Nigeria. However, the results of this study align with and support what was obtained by Aji et al (2020) and Kasri & Chaerunnisa (2020).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These results are interesting for the SCF industry as a whole, because previous studies regarding motivation to utilize Islamic fintech products and services, such as Majid (2021), Darmansyah et al (2020), Purwantini et al (2020), andNiswah et al (2019), found that ATB had no significant effect on BI. In fact, Majid & Nugraha (2022) tested the intention of potential investors to invest through SCF in Indonesia and found the same result, as did Sulaiman et al (2021) when testing the intention to employ syariah-compliant crowdfunding in Nigeria. However, the results of this study align with and support what was obtained by Aji et al (2020) and Kasri & Chaerunnisa (2020).…”
Section: Discussionmentioning
confidence: 78%
“…In Nigeria, the intention of SMEs to implement Islamic crowdfunding is investigated by Kazaure, Abdullah, Zawawi, & Hamzah (2021). Furthermore, the intention to use crowdfunding in Bangladesh is carried out by Munim, Shneor, Adewumi, & Shakil (2020); in China by Kang, Gao, Wang, & Zheng (2016) and Wang, Li, Kang, & Zheng (2019); in Malaysia by Wasiuzzaman, Chong, & Ong (2021); in Brunei Darussalam by Wasiuzzaman, Hj Pungut, & Md Don (2021); in Nigeria by Sulaiman, Muhammad, & Abdulaziz (2021); and in Italy by Troise & Tani (2020) in relation with the equity crowdfunding.…”
Section: Related Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crowdfunding dalam berbagai bentuk (donasi, penghargaan, hutang dan ekuitas) merupakan model baru pembiayaan untuk kegiatan usaha mikro, kecil dan menengah (UMKM) dalam solusi mengatasi kesenjangan permodalan dan implikasi risiko yang dihadapi oleh lembaga keuangan. Bentuk ekuitas dari Crowdfunding telah mendapatkan momentum sebagai sumber pendanaan alternatif bagi wirausahawan, terutama bagi perusahaan start-up (Sulaiman et al, 2021). Crowdfundingyang sesuai syariah memberikan peluang bagi para donatur dan investor UMKM untuk mencapai pembangunan sosial ekonomi dengan pelarangan segala bentuk transaksi berbasis riba.…”
unclassified
“…Crowdfundingyang sesuai syariah memberikan peluang bagi para donatur dan investor UMKM untuk mencapai pembangunan sosial ekonomi dengan pelarangan segala bentuk transaksi berbasis riba. Pembiayaan hendaknya berkaitan dengan sektor riil perekonomian dengan memperhatikan prinsip risiko dan bagi hasil (Sulaiman et al, 2021).…”
unclassified